Utilitarianisme dan Keseimbangan Antara Kepentingan Umum dan Kepentingan Individu - Hananto, V. Andri (Fakultas Hukum Universitas Islam Indonesia, 2025)
One of the most influential schools of legal thought in the world is Utilitarianism. Utilitarianism is built upon the famous maxim of its pioneer, Jeremy Bentham,